PENDIDIKAN ANTI KORUPSI BAGI SISWA - Polontoh, Herry M.; Katjong, Kadir; Yanuaria, Tri; Mulyadi, Dudi (JURNAL PENGABDIAN PAPUA, 2024)
This service was carried out with the title Anti-Corruption Education for MI Yaa Bunaya Students, Waena Village, Heram District, the partners in this service were students in grades 5 and 6 of MI Yaa Bunnaya, this activity was held on Thursday, August 24 2023, which was attended by 40 students. This service is carried out because corruption cases are growing in various circles and have an impact that affects various aspects of national and social life. Eradicating corruption is a series of actions to prevent and eradicate it through coordination, supervision, monitoring, investigation-prosecution and examination in court. Students as part of society have a role in prevention efforts and are expected to become agents of change. Then students are also expected to be able to have a character that is not permissive towards corrupt behavior and acts of corruption. It is hoped that this character can be formed with anti-corruption education taught in formal education at schools. The methods of this service are lectures, discussions, quizzes and anti-corruption poster making competitions. The output of this service is that students have a character that is not permissive towards corrupt behavior and is free from corruption, the availability of propaganda media (banners, posters and stickers) containing anti-corruption campaigns in the school environment. Apart from that, it is also hoped that anti-corruption education will be included as part of the educational curriculum in schools at both primary and secondary school levels.